Francisco Leal Insua and Carlos de Passos. A Distance Friendship - Arias Chachero, Patricia; Vázquez Abuín, Marta (Madrygal. Revista de Estudios Gallegos, 2020)
The writer Francisco Leal Insua and the Portuguese historian Carlos de Passos met through the poet Antonio Noriega Varela, who worked as a teacher in Chavín, near Viveiro, where lived the young Leal Insua. More than 40 years separate them, but this did not prevent an important literary exchange and an honest ideological communion; Noriega introduced Insua in the world of Portuguese Letters and, for more than twenty years, he will maintain epistolary correspondence with the intellectual Carlos de Passos with whom he exchanges articles and publications. Leal Insua and Carlos de Passos finally met in the 50s, in Vigo, where the Galician managed the journal Faro de Vigo.